Defining priorities for future research: results of the UK Kidney Transplant Priority Setting Partnership - Knight, S; Metcalfe, L; O’Donoghue, K; Ball, S; Beale, A; Beale, W; Hilton, R; Hodkinson, K; Lipkin, G; Loud, F; Marson, L; Morris, P (Public Library of Science, 2016)
Background: It has been suggested that the research priorities of those funding and performing research in transplantation may differ from those of end service users such as patients, carers and healthcare professionals involved in day-to-day care. The Kidney Transplant Priority Setting Partnership (PSP) was established with the aim of involving all stakeholders in prioritising future research in the field. Methods: The PSP methodology is as outlined by the James Lind Alliance. An initial survey collected unanswered research questions from patients, carers and clinicians. Duplicate and out-of-scope topics were excluded and the existing literature searched to identify topics answered by current evidence. An interim prioritisation survey asked patients and professionals to score the importance of the remaining questions to create a ranked long-list. These were considered at a final consensus workshop using a modified nominal group technique to agree a final top ten. Results: The initial survey identified 497 questions from 183 respondents, covering all aspects of transplantation from assessment through to long-term follow-up. These were grouped into 90 unanswered “indicative” questions. The interim prioritisation survey received 256 responses (34.8% patients/carers, 10.9% donors and 54.3% professionals), resulting in a ranked list of 25 questions that were considered during the final workshop. Participants agreed a top ten priorities for future research that included optimisation of immunosuppression (improved monitoring, choice of regimen, personalisation), prevention of sensitisation and transplanting the sensitised patient, management of antibody-mediated rejection, long-term risks to live donors, methods of organ preservation, induction of tolerance and bioengineering of organs. There was evidence that patient and carer involvement had a significant impact on shaping the final priorities. Conclusions The final list of priorities relates to all stages of the transplant process, including access to transplantation, living donation, organ preservation, post-transplant care and management of the failing transplant. This list of priorities will provide an invaluable resource for researchers and funders to direct future activity.